On the relation between type-II ion outflow and naturally enhanced ion acoustic lines in the polar ionosphere - Di Loreto, Massimo (UiT Norges arktiske universitet, 2013)
In this work we investigated the relation between type-II ion outflows and NEIALs. Currently, several ion outflows acceleration mechanisms and NEIALs generation theories have been proposed. In the first part of this thesis we review the most important works regarding these two processes. In the second part we present the results of our analysis, together with some unexpected events which were not previously described in the literature. We searched for ion outflow and NEIAL events in the data taken from the 42 m fixed antenna of the EISCAT Svalbard radar. We investigated field aligned ion velocities, electron densities, ion and electron temperatures, temperature ratios and ion fluxes in order to: (1) discuss the starting altitude of both NEIALs and outflows; (2) obtain information about the NEIALs’ generation theories, if they are compatible with our observations and at which altitude range they can be valid. We found some recurring situations for the NEIAL occurrence: particle precipitation and ion outflows are usually involved for events above 300 km, while the few NEIAL events below 200 km that we observed seem to be not always correlated with particle precipitation and not embedded in ion outflows. Our results suggest that each of the three NEIAL generation theories might prevail during its favorite conditions.